2020
DOI: 10.1002/jia2.25472
|View full text |Cite
|
Sign up to set email alerts
|

Missed opportunities to prevent HIV infections among pre‐exposure prophylaxis users: a population‐based mixed methods study, San Francisco, United States

Abstract: Introduction Pre‐exposure prophylaxis (PrEP) is highly effective, although PrEP adherence and persistence has been variable during real world implementation. Little is known about missed opportunities to enhance PrEP adherence among individuals who later HIV seroconverted after using PrEP. The goal of this analysis was to identify all HIV infections among individuals who had accessed PrEP in an integrated health system in San Francisco, and to identify potentially intervenable factors that could have prevented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 40 publications
2
31
1
Order By: Relevance
“…We read with interest Spinelli et al 's study identifying risk factors for HIV acquisition in patients who use HIV Pre-exposure prophylaxis (PrEP) inconsistently [1]. We concur with these findings and have found some similar associations with inconsistent PREP use in our small cohort of patients in Western Sydney.…”
supporting
confidence: 81%
“…We read with interest Spinelli et al 's study identifying risk factors for HIV acquisition in patients who use HIV Pre-exposure prophylaxis (PrEP) inconsistently [1]. We concur with these findings and have found some similar associations with inconsistent PREP use in our small cohort of patients in Western Sydney.…”
supporting
confidence: 81%
“…In a study conducted in San Francisco, CA, one participant identified that depression was a barrier to PrEP adherence, noting the link between depression and substance use as a particular challenge. [ 70 ]. Another study conducted in San Francisco with 25 PrEP users found that mental health problems were associated with adherence difficulties, although participants did not indicate what specific symptoms they experienced [ 50 ].…”
Section: Depressionmentioning
confidence: 99%
“…We agree that stigma related to PrEP or sexual behaviour [2‐4] is an important factor that may interfere with PrEP persistence (consistent use of PrEP during periods with potential HIV exposure) [5]. Participants in this analysis did not report stigma related to being a man who has sex with men (MSM) as a factor in their PrEP gaps, but two participants discussed stigma related to the image of PrEP as a medication for people with multiple sexual partners, and at least one participant feared disclosure of her PrEP use to her partner as she felt it might imply she had outside partners [6].…”
mentioning
confidence: 99%